Brand personality as a direct cause of brand extension success: does self-monitoring matter?. Issue 5 (8th August 2016) - Ferguson, Graham; Lau, Kong Cheen; Phau, Ian
Abstract : Purpose: Focusing on symbolic brands, the current paper re-tests whether perceived 'fit' between the personality of the parent brand and the brand extension causes consumers to the feel increased affect toward the brand extension. The contention is that high brand personality fit causes consumers to like the brand extension more because, like the parent brand, consumers can use the brand extension to maintain and project a desirable self-identity. This relationship is obscured because consumers process brand personality fit as part of the overall brand image fit therefore the potential mediating role of brand image is tested. As well, consumers differ in their self-monitoring disposition, which may explain differences in response to perceived personality fit. Therefore, the potential moderating role of self-monitoring is tested. Design/methodology/approach: Using an experimental design, respondents viewed an advertisement for a brand extension that showed either congruent, moderately incongruent or incongruent personality fit with the parent brand. This was completed for four symbolic brands: two watch brands and two motor vehicle brands. Findings: The results indicate that brand personality fit between the brand extension and the parent brand is causally related to affect felt toward the brand extension but that this relationship is fully mediated by image fit for the BMW brand and partially mediated for VW Beetle, Omega and Swatch. For BMW and Swatch the relationship between the independent variable personality fit and the mediator variable image fit is positively moderated by the self-monitoring disposition of the consumer. Research limitations/implications: The implication is that, while marketers can communicate a wide range of attributes when advertising brand extensions, marketers of symbolic brands should clearly demonstrate brand personality fit as an important component of brand image fit. This is even more important for consumers with a high self-monitoring disposition. Originality/value: The study conclusively tests the importance of personality fit for symbolic brands, the mediating role of brand image, and the interaction effect of self-monitoring on personality fit. These findings contribute to the research literature and help marketers to manage the level of personality fit that should be emphasized in their marketing communications.